Review of studies conducted in nanotechnology education: a meta-synthesis study - Aliye Gocmen; Hilal Karabulut; I. Afşin Kariper (Springer, 2024)
Abstract Nanoscience and Technology (NST) have revolutionized the world. It has led to many innovations since it entered our lives. Meanwhile, the number and quality of people trained in this field gained importance. Currently, initiatives are being taken to integrate this field into the primary education curriculum in many countries. This study focuses on integrating NST into the curriculum as a primary education topic. In this context, meta-synthesis research was used. First, developed countries' well-known initiatives on adapting NST to the curriculum will be discussed in the paper. Then, the works on NST in the literature, especially experimental ones, will be addressed. Finally, based on the results, some suggestions will be made for creating a curriculum in this field. Although there are differences in countries' curriculums, the basic knowledge necessary for education in this field is also outlined.